PENARAPAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE MENGUATKAN KARAKTER SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DI KELAS VI SD NEGERI 137524 TANJUNGBALAI TAHUN PELAJARAN 2017/2018 - SAIMAH . (JURNAL ILMIAH KOHESI, 2018)
The purpose of this study was to determine the character strengthening and improvement of student learning outcomes in learning civic education after the implementation of the Value Clarification Technique learning model in class VI of 137524 Public Elementary School Tanjungbalai 2017/2018 school year. This research is a type of classroom action research with a two cycle design. Each cycle in this study consisted of two teaching and learning activities (KBM). The study was conducted in Public Elementary School 137524 Tanjungbalai for four months starting from September 2017 to December 2017. The subjects used in this study were class VI students of SD Negeri 137524 Tanjungbalai in the 2017/2018 school year, totaling 23 students. Student character data obtained through character observation sheets and student learning outcomes obtained through formative tests. The results of the study show; 1) the Value Clarification Technique learning model strengthens the character of students in learning civic education with character completeness in Cycle I reaching 48% and character completeness in the second cycle reaches 87% with an increase in character completeness by 39%; 2) Value Clarification Technique learning model improves learning outcomes of citizenship education with an assessment of completeness in Cycle I by 83% with an average of 75 and has not yet been completed in a classical manner and in Cycle II of 91% with an average of 86 showing completion individually and class so there was an increase in classical completeness by 8%.